Customary Marriage Between Custom and Law in Algeria A study theoretical - - SALMI, Fatima; DJERADI, Hafsa (Social Sciences Journal, 2018)
Marriage is the basis of family formation, which is a fundamental unit of society, and any imbalance in this foundation will have a profound impact on both the family and the community. Marriage has changed in its types and forms due to the appearance of laws governing it, Among these phenomena is the prevalence of customary marriages, especially among young people in the Arab world, we first explore the nature of the customary marriage and its legitimate rule, as well as its motives and effects in Algerian societ